Association of Motor and Cognitive Symptoms with Health-Related Quality of Life and Caregiver Burden in a German Cohort of Advanced Parkinson's Disease Patients. (24th February 2020) - Klietz, M.; Schnur, T.; Drexel, S.; Lange, F.; Tulke, A.; Rippena, L.; Paracka, L.; Dressler, D.; Höglinger, G. U.; Wegner, F.
Abstract : Parkinson's disease (PD) is a chronic progressive movement disorder with severe reduction in patients' health-related quality of life (HR-QoL). Motor and cognitive symptoms are especially linked with decreased PD patients' HR-QoL. However, the relationship of these symptoms to caregiver burden is relatively unclear. Influence of the Montreal Cognitive Assessment scale (MoCA) as a cognitive screening tool and Movement Disorders Society Unified Parkinson's disease Rating Scale MDS-UPDRS symptoms in relation to patients' HR-QoL and caregivers` burden was analyzed. PD patients ( n  = 124) completed MDS-UPDRS, MoCA, and the PD questionnaire 8 (PDQ-8) as a measure of quality of life. Caregivers ( n  = 78) were assessed by the PD caregiver burden inventory (PDCB). PDQ-8 and PDCB scores were regressed on MDS-UPDRS subscales and MoCA subscores. PDQ-8 correlated with attention ( R 2 0.1282; p < 0.001 ) and executive ( R 2 0.0882; p 0.001) MoCA subscores and all parts of the MDS-UPDRS. PDCB correlated most strongly with MDS-UPDRS part III motor symptoms ( R 2 0.2070; p < 0.001 ) and the MoCA attention subscore ( R 2 0.1815; p < 0.001 ). While all facets of PD symptoms assessed by the MDS-UPDRS relate to PD patients' quality of life, motor symptoms are the most relevant factor for the prediction of caregiver burden. In addition, patients' attentional symptoms seem to affect not only them, but also their caregivers. These findings show the potential of a detailed analysis of MDS-UPDRS and MoCA performance in PD patients.